Evaluation of kanamycin and neomycin resistance in Lactobacillus plantarum using experimental evolution and whole-genome sequencing. (April 2019) - Feng, Cuijiao; Zhang, Fuxin; Wang, Bini; Gao, Jiayuan; Wang, Yin; Shao, Yuyu
Abstract: High antibiotic resistance in the probiotic bacterium Lactobacillus plantarum was achieved using experimental evolution by subculture in the presence of kanamycin and neomycin. After 35 d in the presence of antibiotic, the minimum inhibitory concentration (MIC) of L. plantarum to kanamycin and neomycin were 1024 μg/mL and 256 μg/mL, respectively, which were 64-fold higher than the original isolates. These highly resistant L. plantarum isolates were then subcultured in the absence of antibiotics for 30 d and MIC values decreased to 128 μg/mL and 32 μg/mL at 10 d and 15 d, respectively, but remained constant thereafter. MIC values following subculture in the absence of antibiotic were still above the cut-off value for resistance, indicating that the acquisition of resistance was an irreversible process. Non-synonymous mutations of the resistant isolates were detected by whole-genome sequencing. Of these mutated genes regulating three structural variants (SV) including major facilitator family protein, the ABC transporter substrate binding protein and histidine kinase, were recovered to original state in the absence of antibiotic selection pressure indicating that these mutations played an important role in increasing kanamycin and neomycin resistance in L. plantarum . An evaluation of mobility of resistance genes showed that none of the resistance genes were located on mobile elements in the genome indicating that horizontal gene transfer to other bacteria was impossible. This study provides a way to evaluate antibiotic resistance in L. plantarum regarding its potential safety concern before application in food industry. Highlights: High level resistant Lactobacillus plantarum was selected through experimental evolution. Non-synonymous mutations of the resistant isolates were detected by whole genome sequencing. None of the resistant genes were located on mobile elements through bioinformatics analysis. This study provides a foundation for safe utilization of resistant Lactobacillus plantarum .